A novel HHT and KS statistic approach to detect RoQ attack in wireless sensor network. (20th September 2019) - Chen, Hongsong; Fu, Zhongchuan; Wang, Gang
Reduction of quality (RoQ) attack is a special denial of service (DoS) attack. It is a serious threat to the security of wireless sensor network (WSN). The RoQ attack combines the attack effectiveness and the similarity to normal traffic, so it is difficult to detect by traditional methods. Hilbert-Huang transform (HHT) time frequency analysis method can be utilised to analyse the nonlinear small signal produced by RoQ attack. However, false IMF components are the challenge problems to detect the RoQ attack. Kolmogorov-Smirnov (KS) test approach is proposed to recognise the false intrinsic mode function (IMF) components. CC2530 system-on-chip is selected to build WSN experimental node. Ad hoc on-demand distance vector (AODV) routing protocol and random routing request (RREQ) flooding attack are simulated to implement RoQ attack in Zigbee wireless sensor network. Experimental results demonstrate that the novel approach is effective to detect RoQ attack in Zigbee WSN.